Leading the integration of physician associates into the UK health workforce. (2nd January 2019) - Edwards, Luke D; Till, Alex; McKimm, Judy
Abstract : The introduction of physician associates into the UK health workforce is one of the most significant examples of potentially disruptive innovation in many years, and lessons can be learned from research into the introduction of advanced nurse practitioners. Positive, forward-looking health-care leadership is required at all levels to ensure the successful integration of physician associates into the UK workforce. This review found that organizational culture had an enormous impact on the introduction of advanced nurse practitioners and likewise will affect the integration of physician associates. The most effective strategies facilitated interprofessional, collaborative, collective and inclusive leadership and promoted high staff engagement, the development of proficient interprofessional practitioners, and a clear vision for collaborative practice. In terms of physician associates, such an approach will improve interprofessional and collaborative practice and create the supportive, motivated environment needed to facilitate the introduction of physician associates.